Delays in the presentation to stroke services of patients with transient ischaemic attack and minor stroke. Issue 11 (16th August 2016) - Hurst, K.; Lee, R.; Sideso, E.; Giles, M.; Handa, A.
Abstract : Background: The UK National Institute for Health and Care Excellence (NICE) guidelines state that carotid endarterectomy should be scheduled within 2 weeks of symptoms. The recent National Stroke Strategy has reduced the time interval to 48 h. This study aimed to review the possible delays. Methods: This study analysed patients with confirmed transient ischaemic attack (TIA) or minor stroke, referred to a single tertiary centre clinic and followed up 1 month after the event. A questionnaire was used to collect data on the rapid‐access clinic pathway, and details of previous medication and treatment. Results: Some 150 patients presented with a confirmed TIA or minor stroke during a 5‐month interval (June to October 2014). Fifty‐one (34·0 per cent) had a history of TIA or stroke and 35 (23·3 per cent) had undergone an 'index' event in the 5 days before presentation. Forty‐five patients (30·0 per cent) experienced a reduction or loss of vision. Of this group, 32 had a deficit in vision only, none of whom attributed these symptoms to a cerebrovascular event. Overall 92 (61·3 per cent) of the 150 patients had a delay in presentation to medical services. Forty‐seven (31·3 per cent) had residual symptoms at the clinic appointment. Eighty‐eight patients (58·7 per cent) did not think they were having a stroke and 54 (36·0 per cent) were unaware of the National Stroke Strategy (FAST campaign – Face, Arm, Speech, Time). Conclusion: Two‐thirds of patients were not aware they were having a stroke, one‐third were unaware of the FAST campaign and nearly one‐third presented with eye symptoms. Inclusion of eye symptoms and reaffirmation of the need to react might avoid unnecessary delays in the presentation of patients with TIA and minor stroke. Abstract : FASTER may be better